2012
DOI: 10.5848/apbj.2012.00038
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering as the Way for Productivity and Employability Improvement

Abstract: This paper presents the results of a research that investigated the extent in which volunteering is present in the population of unemployed in Croatia (in Split-Dalmatia county), and in which way volunteering can be a useful way and measure for their faster and more productive (re)employment. Attitudes and perceptions of unemployed volunteers have been compared with those from non-volunteers, as well as unemployment records of those two populations. Finally, the potential of volunteering as a tool for faster a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The link between volunteering and reemployment has been reported in various empirical studies (e.g., Goić & Jeronćić, 2012; Hirst, 2001; Shore & Tashchian, 2013). In a recent national survey conducted in the United States, a significant and stable association between volunteering and employment was found among individuals older than 16 years of age (Spera, Ghertner, Nerino, & DiTommaso, 2013).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The link between volunteering and reemployment has been reported in various empirical studies (e.g., Goić & Jeronćić, 2012; Hirst, 2001; Shore & Tashchian, 2013). In a recent national survey conducted in the United States, a significant and stable association between volunteering and employment was found among individuals older than 16 years of age (Spera, Ghertner, Nerino, & DiTommaso, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Although the emerging adults in this study represent a wide range of careers, skillsets, and sociocultural backgrounds, those who elected to volunteer, even for a minimal investment in time (less than 2 hr per week), were more likely to procure employment 6 months later. Although there is no sufficient evidence in the literature supporting the association between volunteering and likelihood of reemployment (Shore & Tashchian, 2013, Wilson, 2000), there are a few studies that highlight the link between these 2 areas of study (Goić & Jeronćić, 2012; Hirst, 2001; Shore & Tashchian, 2013). It has been suggested that the improvement in career development is implicated in the direct link between volunteering and likelihood of employment volunteering (Ellis, 1993) and that the underlying motivations of those individuals who volunteer, such as increasing social contacts and job-related skills, may increase job prospects (Hall et al, 2006; Hodgkinson & Murray, 1996).…”
Section: Discussionmentioning
confidence: 99%